The challenges of communicating climate change - Carvalho, Anabela (2008)
[Introduction] In an article from 2000 Sheldon Ungar stated that, unlike the ozone hole, climate change never generated a ‘hot crisis’. Looking at the prominence of the issue in the national and international political agendas and the volume of media coverage that it has sustained in the last five years or so one is led to believe that things have changed. A series of remarkable events has contributed to transform climate change into one of the most high profile issues of the present moment: hurricane Katrina, Al Gore’s film and book An Inconvenient Truth, the Nobel prize that was awarded jointly to him and to the IPCC, the Stern Review on the Economics of Climate Change, Live Earth, and the gloomy forecasts of the 4th IPCC Assessment Report all concurred to putting climate change on the media, the public’s and the political agendas, which then tend to feed each other. In fact, multiple surveys indicate that people around the world are aware of the issue and very concerned, are willing to act upon it and expect politicians to take the lead. Yet, global greenhouse gas emissions have continued to rise rapidly.